Designing and Teaching Experiments in Chapter 1: Matter and Energy Metabolism - Biology 11 - Ly, Lai Ngoc; Ngoc, Dao Minh; Quynh, Nguyen Thi Thuy (VNU Journal of Science: Education Research, 2021)
This study is carried out with the aim of designing several experiments for teaching chapter 1 - Matter and Energy Metabolism - Biology 11 as well as evaluating the effectiveness of using experiments in teaching practical competencies-oriented development. We have used various methods such as theoretical research, investigation, consultation, and pedagogical experiment to obtain objective and comprehensive results. The data are then analyzed by the highly reliable mathematical - statistical software. The results obtained in the pedagogical experiment show that using experiment in combination with other active teaching methods has initially brought about effectiveness. Experiments not only help students deepen their knowledge, but also help them build up and develop their practical competence. Therefore, the design and teaching experiments in teaching Biology is an extremely necessary for a highly effective learning.